If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+2(x-4)=4(x-1)+x
We move all terms to the left:
4x+2(x-4)-(4(x-1)+x)=0
We multiply parentheses
4x+2x-(4(x-1)+x)-8=0
We calculate terms in parentheses: -(4(x-1)+x), so:We add all the numbers together, and all the variables
4(x-1)+x
We add all the numbers together, and all the variables
x+4(x-1)
We multiply parentheses
x+4x-4
We add all the numbers together, and all the variables
5x-4
Back to the equation:
-(5x-4)
6x-(5x-4)-8=0
We get rid of parentheses
6x-5x+4-8=0
We add all the numbers together, and all the variables
x-4=0
We move all terms containing x to the left, all other terms to the right
x=4
| 4x+2(x-4)=4(x-1)+x | | 4x+2(x-4)=4(x-1)+x | | 4x+2(x-4)=4(x-1)+x | | -2r+9=- | | 15=9+–3f | | 11x-14=6x+14 | | 11x-14=6x+14 | | 11x-14=6x+14 | | 9x-99=0 | | 15=5a+13 | | 0.02(y-9)+0.08y=0.20y-0.6 | | 0.02(y-9)+0.08y=0.20y-0.6 | | 7–3x=4x–4(2+x | | 7–3x=4x–4(2+x | | 7–3x=4x–4(2+x | | 14v+7=7(+) | | 14v+7=7(+) | | 23-7x=3x-8 | | 9x+1=1x+6 | | 9x+1=1x+6 | | *w/2+8=3 | | *w/2+8=3 | | *w/2+8=3 | | *w/2+8=3 | | *w/2+8=3 | | -7+10x=(-87) | | 54=(x+3)9 | | 124150=5E+08x0.6433 | | -7+10x=(-87) | | 133/y=9 | | x=78x+16 | | k=11,12,13,24 |